Harnessing global fisheries to tackle micronutrient deficiencies - Hicks, Christina C.; Cohen, Philippa J.; Graham, Nicholas A. J.; Nash, Kirsty L.; Allison, Edward H.; D’Lima, Coralie; Mills, David J.; Roscher, Matthew; Thilsted, Shakuntala H.; Thorne-Lyman, Andrew L.; MacNeil, M. Aaron (Nature (London), 2019)
Micronutrient deficiencies account for an estimated one million premature deaths annually, and for some nations can reduce gross domestic product 1 , 2 by up to 11%, highlighting the need for food policies that focus on improving nutrition rather than simply increasing the volume of food produced 3 . People gain nutrients from a varied diet, although fish—which are a rich source of bioavailable micronutrients that are essential to human health 4 —are often overlooked. A lack of understanding of the nutrient composition of most fish 5 and how nutrient yields vary among fisheries has hindered the policy shifts that are needed to effectively harness the potential of fisheries for food and nutrition security 6 . Here, using the concentration of 7 nutrients in more than 350 species of marine fish, we estimate how environmental and ecological traits predict nutrient content of marine finfish species. We use this predictive model to quantify the global spatial patterns of the concentrations of nutrients in marine fisheries and compare nutrient yields to the prevalence of micronutrient deficiencies in human populations. We find that species from tropical thermal regimes contain higher concentrations of calcium, iron and zinc; smaller species contain higher concentrations of calcium, iron and omega-3 fatty acids; and species from cold thermal regimes or those with a pelagic feeding pathway contain higher concentrations of omega-3 fatty acids. There is no relationship between nutrient concentrations and total fishery yield, highlighting that the nutrient quality of a fishery is determined by the species composition. For a number of countries in which nutrient intakes are inadequate, nutrients available in marine finfish catches exceed the dietary requirements for populations that live within 100 km of the coast, and a fraction of current landings could be particularly impactful for children under 5 years of age. Our analyses suggest that fish-based food strategies have the potential to substantially contribute to global food and nutrition security. Nutrient content analyses of marine finfish and current fisheries landings show that fish have the potential to substantially contribute to global food and nutrition security by alleviating micronutrient deficiencies in regions where they are prevalent.